Literacy family context. Relationship between pre-reading skills and successful reading (European Journal of Education and Psychology, 2010)
There are pre-reading skills that are able to prepare students for successful reading. At the same time a literacy family context would be improve early reading acquisition. The main goal of this study was to explore the relationship between the literacy family context and early pre-reading skills acquisitions. Other target was study the pre-reading skills and reading performance interaction. 52 kindergarten children, 5 years old, and from a middle social class were used in this study. Their parents were interviewed with a specific questionnaire made for this research in order to know the literacy family context. Participants’ pre-reading skills were also assessed by the Spanish version of Get Ready to Read! Screening Tool. And the Spanish version of Reading Processes Assessment Test (PROLEG) was used for reading processes assessment when participants got the first grade. Results show statistically significant relations among parent’s education degree and children’s pre-reading skills. Significant correlations between reading performance and children’s pre-reading skills were also found. The main prediction variable for reading performance was phonological awareness.